Parametric Study of Numerically Modelled Delamination Process in a Composite Structure Subjected to Dynamic Loading - MAZURKIEWICZ, Łukasz; DAMAZIAK, Krzysztof; MAŁACHOWSKI, Jerzy; BARANOWSKI, Paweł (Engineering Transactions, 2014)
Composite materials, especially those fibre reinforced, thanks to their advantages, are be- ing used in a growing number of industries. However, the complex structure of these materials results in many analytical problems. One such problematic field is to model failure of a com- posite, and especially the delamination process. The aim of this paper is to find a suitable method of layer connection modelling with the ability to describe delamination phenomena. A few chosen modelling parameters are investigated with respect to a parametric delamination numerical model.